Perlindungan Hukum bagi Pekerja Migran Indonesia: Tantangan dan Strategi Implikasinya - Tohawi, Agus; Miyaskur, Miyaskur; Fitria, Dewi Ulfa Lailatul; Ambodo, Triyo; Iswanto, Juni (JOM, 2024)
This study aims to assess the legal protection of Indonesian migrant workers (PMI) under Law No. 18 of 2017, focusing on how effectively it safeguards their rights throughout the migration process. Utilizing a qualitative research methodology, the study involves a comprehensive review of relevant laws, regulations, and case studies to identify the strengths and weaknesses of the current legal framework. The research findings reveal that while the law outlines essential protections, significant enforcement challenges persist due to bureaucratic inefficiencies, lack of awareness among PMIs regarding their rights, and inadequate support mechanisms in host countries. Furthermore, many PMIs are susceptible to exploitation due to the informal nature of their employment and the difficulties associated with navigating foreign legal systems. The study concludes with strategic recommendations for improving legal protections, such as enhancing inter-agency coordination, implementing awareness and training programs for PMIs, fortifying bilateral agreements with host countries, and establishing effective monitoring systems to ensure compliance. The implications of this research highlight the need for coordinated efforts among government agencies, non-governmental organizations, and international collaborators to improve the welfare and legal protections of Indonesian migrant workers.